2023
DOI: 10.1155/2023/7294334
|View full text |Cite
|
Sign up to set email alerts
|

How Does Servant Leadership Nurture Nurses’ Job Embeddedness? Uncovering Sequential Mediation of Psychological Contract Fulfillment and Psychological Ownership

Abstract: Aim. This research aimed to explore how servant leadership nurtures nurses’ job embeddedness by uncovering the sequential mediation of psychological contract fulfillment and psychological ownership. Background. The healthcare of Pakistan is undergoing an acute shortage of 1.3 million nurses. The gap is widening due to unprecedented natural uncertainties (floods, earthquakes, COVID-19, dengue, polio, and monkeypox) and the large-scale brain drain of nurses. Therefore, exploring the underlying factors that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…The result is consistent with Faraz et al. 's (2023) findings that servant nurse heads will fulfil nursing staff's psychological contracts as servant leaders care about followers' job needs, personal growth and mental health.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The result is consistent with Faraz et al. 's (2023) findings that servant nurse heads will fulfil nursing staff's psychological contracts as servant leaders care about followers' job needs, personal growth and mental health.…”
Section: Discussionsupporting
confidence: 90%
“…When nurses' basic needs are fulfilled, they tend to experience less burnout, stress and psychological illness (Prapanjaroensin et al, 2017). The result is consistent with Faraz et al's (2023) findings that servant nurse heads will fulfil nursing staff's psychological contracts as servant leaders care about followers' job needs, personal growth and mental health.…”
Section: Ta B L Esupporting
confidence: 77%
See 1 more Smart Citation
“…The second step is to improve the leadership of head nurses. The change of leadership styles such as humility, service and agility can adapt to the needs of different new nurses or different stages of the same nurse, so as to exibly adjust the embeddedness of new nurses [20,23]. The third step is to reduce presenteeism.…”
Section: The Indirect Impact Of Nursing Work Environment On Job Embed...mentioning
confidence: 99%
“…Managers' leadership behaviour is considered an in uencing factor for nurses' job embeddedness [19]. Service-oriented leaders can develop psychological contracts with nurses, increase their psychological belongingness, and cultivate job embeddedness [20]. Zhao Mengshu et al found that empowering leadership can provide nurses with more opportunities and resources, enable them to obtain greater autonomy, and improve their work embeddedness level [21].…”
Section: Introductionmentioning
confidence: 99%